Prevalenza delle patologie da sovraccarico biomeccanico degli arti superiori negli addetti del comparto del mobile imbottito / Prevalence of upper limb work-related musculoskeletal disorders (UL-WMSDs) in workers of the upholstered furniture industry - Nicoletti, S.; Carino, M.; Di Leone, et al., G. (La Medicina del Lavoro, 2008)
Il comparto del mobile imbottito, il cosiddetto “triangolo del salotto”, rappresenta una realtà di rilevanza nazionale e di strategica importanza socio-economica nell’area meridionale delle Regioni Puglia e Basilicata. Mediante il coordinamento del network di medici competenti operanti sul territorio, è stata studiata una popolazione di 5.477 lavoratori (esposti n=3481, controlli n=1996, M=3865, F=1612) in 30 aziende del comparto del mobile imbottito per la definizione della prevalenza delle affezioni muscolo-scheletriche da movimenti ripetuti e contro resistenza degli arti superiori (UL-WMSDs). Sono stati considerati tutti i lavoratori in costanza di rapporto di lavoro al 1 gennaio 2003 e tutti i nuovi assunti successivamente fino al 31 dicembre 2003 (in pratica tutti i soggetti sottoposti a sorveglianza sanitaria nel corso dell’anno solare 2003, n=5464). Sono state esaminate le seguenti mansioni: 1) addetto al taglio manuale della pelle con l’ausilio di taglierina manuale 2) addetto alla cucitura del rivestimento in pelle o tessuto 3) addetto alla preparazione del fusto imbottito 4) tappezziere-assemblatore (provvede alla fase terminale di rivestimento del fusto imbottito). I tassi di prevalenza cumulativa di UL-WMSDs al 31.12.03 hanno raggiunto valori del 30% per i gruppi di rischio più esposti. L’indice OCRA presenta una buona correlazione con i tassi di prevalenza. Le patologie di più frequente riscontro sono le cisti tendinee e le tendiniti del polso. Non sembra confermata in questo studio la maggiore suscettibilità del sesso femminile alle UL-WMSDs. Fa eccezione la sindrome del tunnel carpale, che mostra invece una netta predilezione per il sesso femminile. Prevalence of upper limb work-related musculoskeletal disorders (UL-WMSDs) in workers of the upholstered furniture industry Background: The upholstered furniture industry, the so-called “triangle of the sofa industry”’, is a geographic area of national and strategic economic importance in southern Italy. The single tasks are carried out mostly manually, with the characteristics of a handicraft approach. Objectives: The aim of the survey was to assess the prevalence of upper limb work-related musculoskeletal disorders (UL-WMSDs) in 30 factories of the sofa industry located in a large geographic area of the Puglia and Basilicata Regions. Methods: In the period 1 January-31 December 2003 a network of occupational physicians investigated a population of 5.477 subjects (exposed n=3481, controls n=1996, M=3865, F=1612) in 30 different factories of the area. More than 60 percent of the total workforce studied was employed in large-sized companies (>500 employees). The following work tasks were considered: filling preparation workers, leather-cutting operators, sewing and upholstery-assembly workers. Case-definition was assessed through standardized procedures: symptoms by questionnaire plus physical and laboratory/imaging findings. Results: Cumulative prevalence rates of UL-WMSDs as at 31 December 2003 reached values of up to 30% in high risk groups. Prevalence rates showed good correlation with the concise OCRA index used for assessment of exposure to repetitive strain and movements of the upper limb. The most frequently occurring disorders were tendon-related cysts and wrist tendonitis. Shoulder disorders were more frequent in male and female leather-cutting operators. Conclusions: This survey showed a significantly high prevalence of UL-WMSDs in sofa industry workers. It did not seem to be confirmed in this study that there was a greater female susceptibility to UL-WMSDs with the exception of carpal tunnel syndrome: gender difference seems to be less relevant at increasing levels of occupational exposure to repetitive movements and exertion of the upper limbs.